Evaluation of Hot Pepper Genotypes (Capsicum annum) in Western Terai of Nepal - Lohani, Santosh; K.C., Yagya; Shrestha, Surendra Lal (Nepalese Horticulture, 2022)
A set of experiment was conducted to find the best hot pepper genotypes for the Western Terai of Nepal in the October, 2017 and April, 2018 at Agricultural Research Directorate, Lumbini Province, Khajura. The experiments were conducted in Randomized completely block design with four replications. The treatments consisted of hybrid genotypes SV1947HA, SV4884HA, SV2319HA, SV1551HA; two hybrids check cultivars NS 1701 and NCH-1120 and Pusa Jwala which is check open pollinated cultivar of hot pepper. In normal (October) season planting, the highest fresh yield (15.17 t/ha) was obtained from NS 1701 and similar yield was obtained from the genotype SV1947HA (13.86 t/ha) while in the off season (April) planting, the highest fresh yield (7.97 t/ha) was obtained from NCH-1120 and same level of yield with genotypes SV1551HA (6.83 t/ha). Highly significant differences among cultivars were observed in yield and yield attributing characters. Hot pepper yield were observed lower in the April planting due to the crop failure by disease in the heavy rainfall period. The genotypes with better fruit set and yield in respective growing season were needed to be further tested in order to ensure their performance.